Comparison of the preparation conditions for the modification of crumb rubber in laboratory and asphalt plant in terms of rheological properties - Kok, Baha Vural; Yetkin, Z. uelfue; Yalcin, Erkut; Yilmaz, Mehmet (Elsevier Sci Ltd, 2024)
The rise in environmental and economic concerns suggests that there will be a growing reliance on crumb rubber (CR) derived from discarded vehicle tires for bitumen modification in the future. The modification process involving CR is conducted on a large scale, either as a single pass or multi -pass, within specialized plants equipped with mixing equipment and crucially, grinding mills. In the laboratory, CR modification is carried out at different stirring speeds, times and temperatures using different mixing equipment in very small quantities compared to the plant. The extent to which this mixing process in the laboratory is similar to the mixing in the modified plant in the field is an issue that needs to be determined in order to make an efficient pavement design. This study aimed to make the most efficient use of CR modification by comparing laboratory and field conditions in the production of CR modified bitumen. For this purpose, a binder sample with CR additive was taken from the plant. In the laboratory, binders with the same CR content as in the plant were prepared in a high shear mixer at different stirring speed and time. It was found that increasing the stirring speed and time in the laboratory resulted in a binder with superior performance, in particular 4000 rpm and 60-90 minutes mixing conditions produced a binder with improved elastic properties by forming a good CR-bitumen interaction; there were significant differences in the rheological properties between the CR-modified binder produced in the laboratory and in the plant; the performance obtained in the plant can be obtained in the laboratory at low speeds such as 1000-2000 rpm and stirring time of about 30 minutes; the stirring time in the plant should be kept longer than in a single pass to obtain better performance from the binder in the plant.
Keywords: Bitumen; Crumb rubber; Mixing conditions; Plant; Rheological properties